The Importance of East Asian Countries for the Trade in Agri-Food Products Made in the European Union - Pawlak, Karolina (Znaczenie krajów Azji Wschodniej w handlu artykułami rolno-żywnościowymi Unii Europejskiej, 2010)
The aim of the article was to define the role of selected East Asian countries in the EU trade in agri-food products and to examine the competitive position of agri-food products made in the EU on the markets of that region in the years 2000-2007. Selected set of quantitative ex post measures of international competitive position was used in the research. It was proved that in the group of third countries those in East Asia are an important trade partner to the EU in the agri-food sector. From 2000 to 2007 labour-intensive products, especially the animal ones, made in the EU had a strong competitive position on the markets of those countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 229-243
Keywords: export; import; agri-food products; competitive advantege; the European Union; East Asian countries